2018
DOI: 10.3389/fmicb.2018.00192
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in the Spectrum of Spontaneous Rifampicin-Resistance Mutations in the Bacillus subtilis rpoB Gene after Cultivation in the Human Spaceflight Environment

Abstract: The effect of Bacillus subtilis exposure to the human spaceflight environment on growth, mutagenic frequency, and spectrum of mutations to rifampicin resistance (RifR) was investigated. B. subtilis cells were cultivated in Biological Research in Canister-Petri Dish Fixation Units (BRIC-PDFUs) on two separate missions to the International Space Station (ISS), dubbed BRIC-18 and BRIC-21, with matching asynchronous ground controls. No statistically significant difference in either growth or in the frequency of mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 47 publications
(72 reference statements)
0
30
0
Order By: Relevance
“…A majority of studies revealed that the microgravity environment increased the growth rate of microbes (Benoit & Klaus, 2007;Kim et al, 2013;Vukanti, Model, & Leff, 2012). However, some studies showed that no difference was found in the growth rate between space flight and ground control cultures (Coil et al, 2016;Fajardo-Cavazos, Leehan, & Nicholson, 2018). Moreover, a few studies indicated that the flight strain performed significantly decelerated growth compared with the ground control experiment (Fajardo-Cavazos & Nicholson, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…A majority of studies revealed that the microgravity environment increased the growth rate of microbes (Benoit & Klaus, 2007;Kim et al, 2013;Vukanti, Model, & Leff, 2012). However, some studies showed that no difference was found in the growth rate between space flight and ground control cultures (Coil et al, 2016;Fajardo-Cavazos, Leehan, & Nicholson, 2018). Moreover, a few studies indicated that the flight strain performed significantly decelerated growth compared with the ground control experiment (Fajardo-Cavazos & Nicholson, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…For this study, we investigated transcriptomes from bacterial cultures grown in the human spaceflight environment and their corresponding ground control cultures. Spaceflight experiments and organisms included: MESSAGE 2 and BASE A ( Rhodospirillum rubrum strain S1H) 11 ; STS-115 ( Salmonella enterica serovar Typhimurium strain χ3339 and Pseudomonas aeruginosa strain PAO1) 8 , 9 ; STS-123 ( S. enterica serovar Typhimurium strain χ3339) 10 ; BRIC-21 ( Bacillus subtilis strain 168) 22 , 23 ; and BRIC-23 ( B. subtilis strain 168 and Staphylococcus aureus strain UAMS-1) 15 . All of the datasets used are openly available through NASA’s GeneLab Data System (GLDS) repository (genelab.nasa.gov) and are listed in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
“…Bacillus cereus was reportedly altered (Fajardo-Cavazos, 2018;Fajardo-Cavazos & Nicholson, 2016;Guo et al, 2014;Su et al, 2014), and drug resistance persisted in K. pneumoniae and B. subtilis cultured in a spacecraft or in the ISS (Guo et al, 2015;Morrison et al, 2017). Previous studies have reported an increased incidence of mutations in bacteria after spaceflight (Sulzman & Genin, 1994).…”
Section: Sistance Of Staphylococcus Epidermidis Klebsiella Pneumoniamentioning
confidence: 98%
“…Escherichia coli and B. subtilis cultured in space shuttle mission STS‐63 displayed a greater density of cells in the stationary phase, with a shorter lag‐phase (Kacena, Merrell, et al, ). Drug resistance of Staphylococcus epidermidis , Klebsiella pneumoniae , and Bacillus cereus was reportedly altered (Fajardo‐Cavazos, ; Fajardo‐Cavazos & Nicholson, ; Guo et al, ; Su et al, ), and drug resistance persisted in K. pneumoniae and B. subtilis cultured in a spacecraft or in the ISS (Guo et al, ; Morrison et al, ). Previous studies have reported an increased incidence of mutations in bacteria after spaceflight (Sulzman & Genin, ).…”
Section: Introductionmentioning
confidence: 99%